A case of obstructive jaundice caused by metastasis of breast cancer to the intra/extrahepatic bile duct. Issue 1 (20th June 2022) - Suzuki, Yuka; Hoshi, Koki; Tominaga, Keiichi; Inaba, Yasunori; Yoshinaga, Tomonori; Kojimahara, Shunsuke; Maki, Ryuichi; Nemoto, Rena; Tetsuka, Yugo; Kawata, Yosuke; Yamamiya, Akira; Sugaya, Takeshi; et al.
Abstract: A 38‐year‐old woman was admitted to our hospital for a detailed examination of jaundice. Three years before, she had undergone a right total mastectomy and axillary lymph node dissection of her right breast because of cancer. Histopathological evaluation revealed invasive ductal carcinoma. Postoperatively, because multiple bone metastases were found, she underwent chemoradiotherapy. Endoscopic retrograde cholangiopancreatography was performed, which revealed widespread multiple stenoses with a smooth surface from the intrahepatic to the extrahepatic bile duct. A transpapillary biliary biopsy was performed. Histopathological examination revealed adenocarcinoma extending into the subepithelium of the bile duct. The obtained cancer cells were similar to those of the earlier invasive breast cancer. This rare case demonstrates bile duct metastasis of breast cancer with specific endoscopic retrograde cholangiopancreatography findings.